A case of cough, lymphocytic bronchoalveolitis and coeliac disease with improvement following a gluten free diet. Issue 1 (1st January 2002) - Brightling, C E; Symon, F A; Birring, S S; Wardlaw, A J; Robinson, R; Pavord, I D
Abstract : Chronic cough is a common reason for presentation to a respiratory clinic. In up to 20% of cases the cause remains unclear after investigations. We report one such case where there was bronchoscopic evidence of lymphocytic airway inflammation in association with newly diagnosed coeliac disease. All features improved markedly on a gluten free diet, suggesting a causal relationship between coeliac disease, cough, and lymphocytic bronchoalveolitis.